Designing an online work-related language skill for nursing students: A developmental research - Nadia, Hafizhatu; Yansyah, Yansyah; Rafidiyah, Dina (JEES (Journal of English Educators Society), 2021)
Technology brings opportunities to extend the learning environment outside the classroom. An online course can be an extracurricular activity which allows the students to learn English for their career preparation. This article reports a developmental research for designing an online learning module for nursing students to pursue their career abroad. One English teacher and 40 nursing students from a private university participated in this research. Interview and questionnaire were employed to collect the data regarding the students’ need, usability, and the implementation of the product during the field try out. Two experts were also invited to evaluate the quality of the product’s content and instructional technology. The result of this developmental study is an online course and a workbook to accompany the students learning. The findings reveal that online learning has an opportunity to help students to shape their work-related language skills at home. The challenges for the implementation of this course are also discussed.